Gender Dependence In Mouth Opening Dimensions In Normal Adult Malaysians Population - Ramizu Shaari; Teoh Eng Hwa; Shaifulizan Abdul Rahman (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
While measurement of mouth opening is an important clinica examination in diagnosis and management of oral disease, data on non-Western populations are limited. This study was therefore conducted to determine the range of mouth opening in normal Malaysian male and female adults. A total of 34 dental students of Universiti Sains Malaysia (USM) were chosen randomly and their maximum mouth opening was measured after being asked to open their mouth sufficiently to accommodate three fingers. Measurement was performed from the edge of the upper incisor to the lower incisor using a caliper divider. The difference of median values between male (47.6 mm) and female (40.8 mm) were significant respectively (p<0.05). Thus the width of mouth opening in Malaysian student population is gender dependent although further study with a larger sample size and with other ethnic groups should be carried out, focusing on age.